Monitoring Biotic and Abiotic Stress in Crop Plants through Remote Sensing - Prasad, P. N. Siva; Lakshman, K. (Chronicle of Bioresource Management, 2023)
Determination of plant stress factors is challenging as it can be a compound result of water deficit, nutrient deficiency and disease infection. Symptoms arising from these stress factors may also be similar. Hence, visual observation alone could result in flawed diagnosis which would eventually disrupt remedial action for the affected plants. Spectral reflectance measurements help to identify and select wavelengths sensitive to different types of plant stress. Use of Remote sensing (RS) to monitor the crop affected by biotic and abiotic stress is based on the assumption that stress interferes with photosynthesis and physical structure of the plant at tissue and canopy level, and thus affects the absorption of light energy and alters the reflectance spectrum. Research into vegetative spectral reflectance can help us gain a better understanding of the physical, physiological and chemical processes altered in affected plants due to stress and to detect cause by different stress factors